Les tumultes chez Machiavel et la langue de la jurisprudence - Angela De Benedictis (Astérion, 2016)
In recent years, scholars of Machiavelli have dedicated closer attention to, on one hand, the role played by tumults, and the presence of the language of jurisprudence in his work. Until now, these two readings of Machiavelli have never intersected. This essay aims to show to what extent the language of jurisprudence was present in Machiavelli’s writings on tumults both in his early works, and above all in the Florentine Histories. Starting from Machiavelli’s analysis of the Valdichiana rebellion (1503), the first part of the essay deals with ‘rebellion’ as a legal and political issue, as a specific case of the crime of lese majesty, discussed among civil and canon lawyers from commentaries on the famous imperial laws of Henry VII (1313) up through some legal consilia written in defense of Lorenzo de’ Medici and the city of Florence in relation to the Pazzi Conspiracy (1478), as well as first treatise dedicated specifically to the subject of seditions by a French jurist (1515). The essay’s second part considers the famous speech of the anonymous Ciompo in the third book of the Florentine Histories, and analyses a passage commonly overlooked by scholars : “When many err, no one is punished”. The essay shows that in this passage Machiavelli used a juridical principle, a regula iuris, which was certainly controversial and very frequently not accepted, but theoretically admitted as such. In concluding, the essay proposes some possible paths for further researchs.